THE PROFILE OF ENGLISH EXAMINATION RESULTS OF SENIOR HIGH SCHOOLS IN NUNUKAN REGENCY - Aisyah, Siti; Ridwan, Ridwan; Hajar, Siti (Universitas Borneo Tarakan, 2022)
This research aimed to find out whether there was any significant difference in English National Examination results by considering school status, school accreditation, major, gender, and studentsâ€™ achievement. This research employed a causal-comparative design. The sample of this research was 1,728 students of Senior High Schools in Nunukan regency in the 2018/2019 academic year. Based on the results of data analysis, it was found that (1) the students in public schools were better than those in private schools, (2) the school accreditations did not give any differences in the English National Examination results where the schools with lower accreditation apparently had better English National examination results, (3) the students in natural science were better than those in social science, (4) the female students were better than male students, and (5) the English national examination results were in a low category. The students who got higher scores in English National Examination would acquire higher scores in National Examination (NUN).Â